Sea Lice ( Lepeophtheirus salmonis ) Harbour Putative Fish Pathogens: Insights From Illumina and Nanopore Sequencing - B. Klimesova; N. M. Ruane; R. Domingo‐Bretón; F. Moroni; F. Naya‐Català; J. Pérez‐Sánchez; K. O'Dwyer; O. Lyashevska; H. Rodger; A. Talbot (Journal of Fish Diseases, 2026)
Ectoparasites that penetrate host skin can act as biological or mechanical vectors for pathogens and, in some cases, serve as reservoirs. Crustacean ectoparasites of fish are potential vectors of pathogens, which is especially relevant for obligate pathogens (e.g., Aeromonas salmonicida ) with limited seawater survival. Sea lice ( Lepeophtheirus salmonis ), affecting Atlantic salmon, cause dermal damage and can facilitate secondary infections, resulting in economic losses. While the physical impact of sea lice is well known, their role in pathogen transmission is less clear. The gut bacterial microbiome of lice collected over four months from a salmon farm in Ireland was analysed using Illumina MiSeq and Oxford Nanopore Technologies (ONT) PromethION sequencing for comparison. Illumina and Nanopore sequencing identified 15 and 24 genera of known fish pathogens, respectively. Moreover, Nanopore data revealed up to 15 putative pathogenic species, including Tenacibaculum maritimum , T. dicentrarchi and Vibrio anguillarum , causative agents of tenacibaculosis and vibriosis. The results of this study provide a gut bacterial microbiome characterisation of L. salmonis in a commercial aquaculture setting and demonstrate the potential of sea lice to act as pathogen vectors or reservoirs. These findings have important implications for pathogen surveillance, management, and prevention strategies in salmon aquaculture.

Hydrogen, single-carbon compounds, and thermal regime in the oceanic ultramafic-dominated lithosphere: insights from a deep borehole on the Atlantis Massif - Susan Q. Lang; C. Geoffrey Wheat; Kristin L. Dickerson; Mark K. Reagan; Ivan P. Savov; Jordyn A. Robare; William J. Brazelton; Johanna Suhonen; Oscar Cavazos; Andrew McCaig; Peter Blum; Natsue Abe; et al. (Geochimica et Cosmochimica Acta, 2025)

The Microbial Trojan Horse and Antimicrobial Resistance: Acanthamoeba as an Environmental Reservoir for Multidrug Resistant Bacteria - Ronnie Mooney; Erin Corbett; Elisa Giammarini; Kiri Rodgers; Carla Donet; Ernest Mui; Arhama T. A. Ansari; Ayush Ransingh; Pradnya S. Vernekar; Harleen K. Walia; Jyoti Sharma; John Connolly; et al. (Environmental Microbiology, 2025)
Antimicrobial resistance (AMR) is shaped by environmental pressures, yet the role of microbial predators such as Acanthamoeba in resistance dynamics remains poorly characterized. In this study, Acanthamoeba ‐associated bacterial communities (AAB) exhibited significantly higher multidrug resistance than sediment‐associated bacterial communities (SAB) in a polluted estuarine system. All isolated amoebae belonged to the T4 genotype, suggesting selection for resilient host organisms. AAB displayed elevated multiple antibiotic resistance (MAR) indices and increased resistance to multiple antibiotic classes, particularly aminoglycosides, macrolides, fluoroquinolones and β‐lactams. Correlation analysis revealed that resistance in AAB, but not SAB, was associated with potentially toxic elements (PTEs) known to influence phagocyte survival, including arsenic, vanadium, and calcium. These elements may select for traits that confer metal and antibiotic resistance. The findings support a model where protists act as selective environments for AMR, favoring bacteria that possess enhanced tolerance mechanisms. This work provides the first direct evidence linking PTE exposure to the intracellular resistome of Acanthamoeba ‐associated bacteria. It underscores the need for AMR monitoring frameworks that include protist‐bacteria interactions, with implications for One Health and environmental risk assessment strategies. Moreover, this approach is scalable for application in low/middle‐income countries, where AMR burden is greatest and surveillance capacity remains limited.

P30-23 Boosting Early-Stage ADC Toxicity assessment through human in vitro cell models - B. Recolin; C. Rodger; J. Caruana Santiago; S. Randle; R. Foreman; K. Khan; M. Barbara; J. Kwon; R. Lucey; K. Pryde; M.-Y. Lee; S. Liu; et al. (Toxicology Letters, 2025)

In vitro micropropagation of critically imperiled Crocanthemum canadense (Cistaceae) and identification of endomycorrhizal symbionts - Kendra Sampson; Rodger C. Evans; Robin Browne; Allison K. Walker (Plant Cell, Tissue and Organ Culture (PCTOC), 2024)

Vivaria housing conditions expose sex differences in brain oxidation, microglial activation, and immune system states in aged hAPOE4 mice - E. M. Reyes-Reyes; J. Brown; M. D. Trial; D. Chinnasamy; J. P. Wiegand; D. Bradford; R. D. Brinton; K. E. Rodgers (Experimental Brain Research, 2024)
Apolipoprotein E ε4 allele (APOE4) is the predominant genetic risk factor for late-onset Alzheimer’s disease (AD). APOE4 mouse models have provided advances in the understanding of disease pathogenesis, but unaccounted variables like rodent housing status may hinder translational outcomes. Non-sterile aspects like food and bedding can be major sources of changes in rodent microflora. Alterations in intestinal microbial ecology can cause mucosal barrier impairment and increase pro-inflammatory signals. The present study examined the role of sterile and non-sterile food and housing on redox indicators and the immune status of humanized- APOE4 knock-in mice (hAPOe4). hAPOE4 mice were housed under sterile conditions until 22 months of age, followed by the transfer of a cohort of mice to non-sterile housing for 2 months. At 24 months of age, the redox/immunologic status was evaluated by flow cytometry/ELISA. hAPOE4 females housed under non-sterile conditions exhibited: (1) higher neuronal and microglial oxygen radical production and (2) lower CD68 + microglia (brain) and CD8 + T cells (periphery) compared to sterile-housed mice. In contrast, hAPOE4 males in non-sterile housing exhibited: (1) higher MHCII + microglia and CD11b + CD4 + T cells (brain) and (2) higher CD11b + CD4 + T cells and levels of lipopolysaccharide-binding protein and inflammatory cytokines in the periphery relative to sterile-housed mice. This study demonstrated that sterile vs. non-sterile housing conditions are associated with the activation of redox and immune responses in the brain and periphery in a sex-dependent manner. Therefore, housing status may contribute to variable outcomes in both the brain and periphery.

Recovery of multireassortant bluetongue virus serotype 6 sequences from a mule deer (Odocoileus hemionus) and Dorset sheep (Ovis aries) in Colorado - Molly J. Carpenter; Case R. Rodgers; Mia K. Torchetti; Karen A. Fox; Mollie Burton; Tyler J. Sherman; Christie E. Mayo (Veterinary Microbiology, 2024)

Does reward regulate habitual consumption behaviour? - Amy Rodger; Lawrence W. Barsalou; Esther K. Papies (Appetite, 2023)

Study of fast in-line measurement techniques for water ice characterization - Carolina Cruz; Cláudio P. Fonte; Antonio De Simone; Felix K. Oppong; Will Jeatt; Thomas L. Rodgers (Journal of Food Engineering, 2023)

Can a simple plan change a complex behavior? Implementation intentions in the context of water drinking - Amy Rodger; Ariel Vezevicius; Esther K. Papies (Appetite, 2023)

Modeling genetic benefits and financial costs of integrating biobanking into the conservation breeding of managed marsupials - Lachlan G. Howell; Peter R. Mawson; Pierre Comizzoli; Ryan R. Witt; Richard Frankham; Simon Clulow; Justine K. O'Brien; John Clulow; Paul Marinari; John C. Rodger (Conservation Biology, 2023)
Managed breeding programs are an important tool in marsupial conservation efforts but may be costly and have adverse genetic effects in unavoidably small captive colonies. Biobanking and assisted reproductive technologies (ARTs) could help overcome these challenges, but further demonstration of their potential is required to improve uptake. We used genetic and economic models to examine whether supplementing hypothetical captive populations of dibblers ( Parantechinus apicalis ) and numbats ( Myrmecobius fasciatus ) with biobanked founder sperm through ARTs could reduce inbreeding, lower required colony sizes, and reduce program costs. We also asked practitioners of the black‐footed ferret ( Mustela nigripes ) captive recovery program to complete a questionnaire to examine the resources and model species research pathways required to develop an optimized biobanking protocol in the black‐footed ferret. We used data from this questionnaire to devise similar costed research pathways for Australian marsupials. With biobanking and assisted reproduction, inbreeding was reduced on average by between 80% and 98%, colony sizes were on average 99% smaller, and program costs were 69‐ to 83‐fold lower. Integrating biobanking made long‐standing captive genetic retention targets possible in marsupials (90% source population heterozygosity for a minimum of 100 years) within realistic cost frameworks. Lessons from the use of biobanking technology that contributed to the recovery of the black‐footed ferret include the importance of adequate research funding (US$4.2 million), extensive partnerships that provide access to facilities and equipment, colony animals, appropriate research model species, and professional and technical staff required to address knowledge gaps to deliver an optimized biobanking protocol. Applied research investment of A$133 million across marsupial research pathways could deliver biobanking protocols for 15 of Australia's most at‐risk marsupial species and 7 model species. The technical expertise and ex situ facilities exist to emulate the success of the black‐footed ferret recovery program in threatened marsupials using these research pathways. All that is needed now for significant and cost‐effective conservation gains is greater investment by policy makers in marsupial ARTs.

Sources and concentrations of methane, ethane, and CO2 in deep aquifers of the Surat Basin, Great Artesian Basin - J.K. Pearce; H. Hofmann; K. Baublys; S.D. Golding; I. Rodger; P. Hayes (International Journal of Coal Geology, 2023)

Seismic surveys near gray whale feeding areas off Sakhalin Island, Russia: assessing impact and mitigation effectiveness - Lisanne Aerts; Michael R. Jenkerson; Vladimir E. Nechayuk; Glenn Gailey; Roberto Racca; Arny L. Blanchard; Lisa K. Schwarz; H. Rodger Melton (Environmental Monitoring and Assessment, 2022)
In 2015, two oil and gas companies conducted seismic surveys along the northeast coast of Sakhalin Island, Russia, near western gray whale ( Eschrichtius robustus ) feeding areas. This population of whales was listed as Critically Endangered at the time of the operations described here but has been reclassified as Endangered since 2018. The number and duration of the 2015 seismic surveys surpassed the level of previous seismic survey activity in this area, elevating concerns regarding disturbance of feeding gray whales and the potential for auditory injury. Exxon Neftegas Limited (ENL) developed a mitigation approach to address these concerns and, more importantly, implemented a comprehensive data collection strategy to assess the effectiveness of this approach. The mitigation approach prioritized completion of the seismic surveys closest to the nearshore feeding area as early in the season as possible, when fewer gray whales would be present. This was accomplished by increasing operational efficiency through the use of multiple seismic vessels and by establishing zones with specific seasonal criteria determining when air gun shutdowns would be implemented. These zones and seasonal criteria were based on pre-season modeled acoustic footprints of the air gun array and on gray whale distribution data collected over the previous 10 years. Real-time acoustic and whale sighting data were instrumental in the implementation of air gun shutdowns. The mitigation effectiveness of these shutdowns was assessed through analyzing short-term behavioral responses and shifts in gray whale distribution due to sound exposure. The overall mitigation strategy of an early survey completion was assessed through bioenergetics models that predict how reduced foraging activity might affect gray whale reproduction and maternal survival. This assessment relied on a total of 17 shore-based and 5 vessel-based teams collecting behavior, distribution, photo-identification, prey, and acoustic data. This paper describes the mitigation approach, the implementation of mitigation measures using real-time acoustic and gray whale location data, and the strategy to assess impacts and mitigation effectiveness.

The Society for Environmental Geochemistry and Health (SEGH): building for the future of early career researchers - O. S. Humphrey; D. R. S. Middleton; S. Ahmad; T. Cocerva; S. M. Dowell; R. Garza-Galndo; E. M. Hamilton; N. Kafwamfwa; B. Kaninga; P. Kourgia; I. S. Ligowe; H. A. MacLeod; et al. (Environmental Geochemistry and Health, 2021)

Encapsulating Polyethyleneimine-DNA Nanoplexes into PEGylated Biodegradable Microparticles Increases Transgene Expression In Vitro and Reduces Inflammatory Responses In Vivo - Treniece L. Terry; Brittany E. Givens; Andrea Adamcakova-Dodd; Peter S. Thorne; Victor G. J. Rodgers; Aliasger K. Salem (AAPS PharmSciTech, 2021)

Morbidity compression or expansion? A temporal analysis of the age at onset of non-communicable diseases in India - Sanjay K. Mohanty; Justin Rodgers; Rajeev R. Singh; Radhe Shyam Mishra; Rockli Kim; Junaid Khan; Priyamadhaba Behera; S. V. Subramanian (GeroScience, 2021)

Threats posed to conservation by media misinformation - Adam G. Hart; Rosie Cooney; Amy Dickman; Darragh Hare; Charles Jonga; Paul K. Johnson; Maxi Pia Louis; Rodgers Lubilo; Dilys Roe; Catherine Semcer; Keith Somerville (Conservation Biology, 2020)

Kinematic Rupture Modeling of Ground Motion from the M7 Kumamoto, Japan Earthquake - A. Pitarka; R. Graves; K. Irikura; K. Miyakoshi; A. Rodgers (Pure and Applied Geophysics, 2020)

Low-intensity repetitive transcranial magnetic stimulation over prefrontal cortex in an animal model alters activity in the auditory thalamus but does not affect behavioural measures of tinnitus - Wilhelmina H. A. M. Mulders; K. Leggett; V. Mendis; H. Tarawneh; J. K. Wong; J. Rodger (Experimental Brain Research, 2019)

Tunable Properties of Poly-DL-Lactide-Monomethoxypolyethylene Glycol Porous Microparticles for Sustained Release of Polyethylenimine-DNA Polyplexes - Treniece L. Terry; Brittany E. Givens; Victor G. J. Rodgers; Aliasger K. Salem (AAPS PharmSciTech, 2019)

Analysis of novel domain-specific mutations in the zebrafish ndr2/cyclops gene generated using CRISPR-Cas9 RNPs - Ashley N. Turner; Reagan S. Andersen; Ivy E. Bookout; Lauren N. Brashear; James C. Davis; David M. Gahan; John P. Gotham; Baraa A. Hijaz; Ashish S. Kaushik; Jordan B. Mcgill; Victoria L. Miller; Zachariah P. Moseley; et al. (Journal of Genetics, 2018)

Investigation of co‐infections with pathogens associated with gill disease in Atlantic salmon during an amoebic gill disease outbreak - J K Downes; T Yatabe; M Marcos‐Lopez; H D Rodger; E MacCarthy; I O'Connor; E Collins; N M Ruane (Journal of Fish Diseases, 2018)
Gill diseases are a complex and multifactorial challenge for marine farmed Atlantic salmon. Co‐infections with putative pathogens are common on farms; however, there is a lack of knowledge in relation to the potential effect co‐infections may have on pathology. The objective of this study was to determine the prevalence and potential effects of Neoparamoeba perurans, Desmozoon lepeophtherii , Candidatus Branchiomonas cysticola, Tenacibaculum maritimum and salmon gill poxvirus ( SGPV ) during a longitudinal study on a marine Atlantic salmon farm. Real‐time PCR was used to determine the presence and sequential infection patterns of these pathogens on gill samples collected from stocking until harvest. A number of multilevel models were used to determine the effect of these putative pathogens on gill health (measured as gill histopathology score), while adjusting for the effect of water temperature and time since the last freshwater treatment. Results indicate that between 12 and 16 weeks post‐seawater transfer (wpst), colonization of the gills by all pathogens had commenced and by week 16 of marine production each of the pathogens had been detected. D. lepeophtherii and Candidatus B. cysticola were by far the most prevalent of the potential pathogens detected during this study. Detections of T. maritimum were found to be significantly correlated with temperature showing distinct seasonality. Salmon gill poxvirus was found to be highly sporadic and detected in the first sampling point, suggesting a carryover from the freshwater stage of production. Finally, the model results indicated no clear effect between any of the pathogens. Additionally, the models showed that the only variable which had a consistent effect on the histology score was N. perurans .

Genomes of ubiquitous marine and hypersaline Hydrogenovibrio , Thiomicrorhabdus and Thiomicrospira spp. encode a diversity of mechanisms to sustain chemolithoautotrophy in heterogeneous environments - Kathleen M. Scott; John Williams; Cody M. B. Porter; Sydney Russel; Tara L. Harmer; John H. Paul; Kirsten M. Antonen; Megan K. Bridges; Gary J. Camper; Christie K. Campla; Leila G. Casella; Eva Chase; et al. (Environmental Microbiology, 2018)
Summary Chemolithoautotrophic bacteria from the genera Hydrogenovibrio, Thiomicrorhabdus and Thiomicrospira are common, sometimes dominant, isolates from sulfidic habitats including hydrothermal vents, soda and salt lakes and marine sediments. Their genome sequences confirm their membership in a deeply branching clade of the Gammaproteobacteria . Several adaptations to heterogeneous habitats are apparent. Their genomes include large numbers of genes for sensing and responding to their environment (EAL‐ and GGDEF‐domain proteins and methyl‐accepting chemotaxis proteins) despite their small sizes (2.1–3.1 Mbp). An array of sulfur‐oxidizing complexes are encoded, likely to facilitate these organisms' use of multiple forms of reduced sulfur as electron donors. Hydrogenase genes are present in some taxa, including group 1d and 2b hydrogenases in Hydrogenovibrio marinus and H. thermophilus MA2‐6, acquired via horizontal gene transfer. In addition to high‐affinity cbb 3 cytochrome c oxidase, some also encode cytochrome bd‐ type quinol oxidase or ba 3 ‐ type cytochrome c oxidase, which could facilitate growth under different oxygen tensions, or maintain redox balance. Carboxysome operons are present in most, with genes downstream encoding transporters from four evolutionarily distinct families, which may act with the carboxysomes to form CO 2 concentrating mechanisms. These adaptations to habitat variability likely contribute to the cosmopolitan distribution of these organisms.

Reshaping structural hysteresis response with semi-active viscous damping - N. K. Hazaveh; G. W. Rodgers; J. G. Chase; S. Pampanin (Bulletin of Earthquake Engineering, 2017)

Evaluation of Non-destructive Molecular Diagnostics for the Detection of Neoparamoeba perurans - Jamie K. Downes; Megan L. Rigby; Richard S. Taylor; Ben T. Maynard; Eugene MacCarthy; Ian O'Connor; Mar Marcos-Lopez; Hamish D. Rodger; Evelyn Collins; Neil M. Ruane; Mathew T. Cook (Frontiers in Marine Science, 2017)

Technical pre‐analytical effects on the clinical biochemistry of Atlantic salmon ( Salmo salar L.) - M Braceland; K Houston; A Ashby; C Matthews; H Haining; H Rodger; P D Eckersall (Journal of Fish Diseases, 2017)
Clinical biochemistry has long been utilized in human and veterinary medicine as a vital diagnostic tool, but despite occasional studies showing its usefulness in monitoring health status in Atlantic salmon ( Salmo salar L.), it has not yet been widely utilized within the aquaculture industry. This is due, in part, to a lack of an agreed protocol for collection and processing of blood prior to analysis. Moreover, while the analytical phase of clinical biochemistry is well controlled, there is a growing understanding that technical pre‐analytical variables can influence analyte concentrations or activities. In addition, post‐analytical interpretation of treatment effects is variable in the literature, thus making the true effect of sample treatment hard to evaluate. Therefore, a number of pre‐analytical treatments have been investigated to examine their effect on analyte concentrations and activities. In addition, reference ranges for salmon plasma biochemical analytes have been established to inform veterinary practitioners and the aquaculture industry of the importance of clinical biochemistry in health and disease monitoring. Furthermore, a standardized protocol for blood collection has been proposed.

An outbreak of francisellosis in wild‐caught C eltic S ea A tlantic cod, G adus morhua L., juveniles reared in captivity - N M Ruane; M Bolton‐Warberg; H D Rodger; D J Colquhoun; M Geary; S J McCleary; K O'Halloran; K Maher; D O'Keeffe; L Mirimin; K Henshilwood; F Geoghegan; et al. (Journal of Fish Diseases, 2015)

Trait differences in response to chronic nicotine and nicotine withdrawal in rats - K. Z. Kolokotroni; R. J. Rodgers; A. A. Harrison (Psychopharmacology, 2014)

Differential characterization of emerging skin diseases of rainbow trout – a standardized approach to capturing disease characteristics and development of case definitions - B Oidtmann; S E LaPatra; D Verner‐Jeffreys; M Pond; E J Peeler; P A Noguera; D W Bruno; S St‐Hilaire; C B Schubiger; K Snekvik; M Crumlish; D M Green; et al. (Journal of Fish Diseases, 2013)
Farmed and wild salmonids are affected by a variety of skin conditions, some of which have significant economic and welfare implications. In many cases, the causes are not well understood, and one example is cold water strawberry disease of rainbow trout, also called red mark syndrome, which has been recorded in the UK since 2003. To date, there are no internationally agreed methods for describing these conditions, which has caused confusion for farmers and health professionals, who are often unclear as to whether they are dealing with a new or a previously described condition. This has resulted, inevitably, in delays to both accurate diagnosis and effective treatment regimes. Here, we provide a standardized methodology for the description of skin conditions of rainbow trout of uncertain aetiology. We demonstrate how the approach can be used to develop case definitions, using coldwater strawberry disease as an example.

Co‐Infection with Pseudomonas anguilliseptica and Delftia acidovorans in the European eel, Anguilla anguilla (L.): a case history of an illegally trafficked protected species - K B Andree; C J Rodgers; D Furones; E Gisbert (Journal of Fish Diseases, 2013)
Inspections by customs agents at Barcelona airport discovered 420 kg of contraband glass eels prepared for shipment to Hong Kong. After confiscation of these animals by police, they were transported to holding facilities to be maintained until after a judicial hearing. Upon arrival, they were separated into two groups and held under ambient flow‐through conditions in fresh water. During their captivity period, several peaks in mortality occurred and multiple bacterial strains were isolated from moribund animals. Sequencing of 16S rDNA was used to determine specific identity of the isolates. An initial isolation of Pseudomonas anguilliseptica was treated with oxytetracycline. A subsequent isolation of Delftia acidovorans proved resistant to oxytetracycline and was treated with gentamicin in combination with sulphadiazine–trimethoprim. Once the health condition of the animals was stabilized, they were partitioned into groups and subsequently released as part of a restocking effort for the species following the guidelines of Regulation (EC) 1100/2007 (Anon 2007). This represents the first record for both bacterial species in the host Anguilla anguilla in the Spanish Mediterranean.

Use of Integrated Landscape Indicators to Evaluate the Health of Linked Watersheds and Coral Reef Environments in the Hawaiian Islands - Ku‘ulei S. Rodgers; Michael H. Kido; Paul L. Jokiel; Tim Edmonds; Eric K. Brown (Environmental Management, 2012)

Effects of chronic nicotine, nicotine withdrawal and subsequent nicotine challenges on behavioural inhibition in rats - K. Z. Kolokotroni; R. J. Rodgers; A. A. Harrison (Psychopharmacology, 2012)

Versican induces a pro-metastatic ovarian cancer cell behavior which can be inhibited by small hyaluronan oligosaccharides - Miranda P. Ween; Katja Hummitzsch; Raymond J. Rodgers; Martin K. Oehler; Carmela Ricciardelli (Clinical & Experimental Metastasis, 2011)

Epitheliocystis in Atlantic salmon, Salmo salar L., farmed in fresh water in Ireland is associated with ‘ Candidatus Clavochlamydia salmonicola’ infection - S O Mitchell; T Steinum; H Rodger; C Holland; K Falk; D J Colquhoun (Journal of Fish Diseases, 2010)
Intracellular inclusions containing chlamydia‐like organisms are frequently observed in the gill epithelial cells of Atlantic salmon, Salmo salar L., cultured in fresh water in Ireland. In this study, the causative agent was identified in four separate freshwater sites, using 16s rRNA sequencing, as ‘ Candidatus Clavochlamydia salmonicola’. Histopathology and real‐time (RT) PCR were used to further assess infections. The prevalence of infection ranged from 75–100% between sites and infection intensity was highly variable. No significant lesions were associated with these infections. As a diagnostic tool, RT‐PCR proved marginally more sensitive than histopathology. The fate of ‘ Candidatus Clavochlamydia salmonicola’ in Atlantic salmon post‐seawater transfer was investigated in a 12‐week marine longitudinal study. Both RT‐PCR and histopathological examination indicate that the organism disappears from the gills 4–6 weeks post‐transfer.

Source mechanisms of the June 2004 Tabuk earthquake sequence, Eastern Red Sea margin, Kingdom of Saudi Arabia - K. S. Aldamegh; K. M. Abou Elenean; H. M. Hussein; A. J. Rodgers (Journal of Seismology, 2009)

The invasive species Alliaria petiolata (garlic mustard) increases soil nutrient availability in northern hardwood-conifer forests - Vikki L. Rodgers; Benjamin E. Wolfe; Leland K. Werden; Adrien C. Finzi (Oecologia, 2008)

Ocean acidification and calcifying reef organisms: a mesocosm investigation - P. L. Jokiel; K. S. Rodgers; I. B. Kuffner; A. J. Andersson; E. F. Cox; F. T. Mackenzie (Coral Reefs, 2008)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Graded ephrin-A2 expression in the developing hamster superior colliculus - Sherralee S. Lukehurst; Carolyn E. King; Lyn D. Beazley; David K. C. Tay; Kwok-Fai So; Jennifer Rodger (Experimental Brain Research, 2006)

Interannual-to-decadal variability of North Atlantic air-sea CO 2 fluxes - S. Raynaud; J. C. Orr; O. Aumont; K. B. Rodgers; P. Yiou (Ocean Science, 2006)
The magnitude of the interannual variability of North Atlantic air-sea CO2 fluxes remains uncertain. Interannual extremes simulated by atmospheric inverse approaches are typically about ±0.3 Pg C yr−1, whereas those from ocean models are less than ±0.1 Pg C yr−1. Thus variability in the North Atlantic is either about 60% or less than 20% of the global variability of about ±0.5 Pg C yr−1 (as estimated by both approaches). Here we explore spatiotemporal variability within the North Atlantic basin of one ocean model in order to more fully describe potential counteracting trends in different regions that may explain why basin-wide variability is small relative to global-scale variability. Typical atmospheric inverse approaches separate the North Atlantic into at most a few regions and thus cannot properly simulate such counteracting effects. For this study, two simulations were made with a biogeochemical model coupled to a global ocean general circulation model (OGCM), which itself was forced by 55-year NCEP reanalysis fields. In the first simulation, atmospheric CO2 was maintained at the preindustrial level (278 ppmv); in the second simulation, atmospheric CO2 followed the observed increase. Simulated air-sea CO2 fluxes and associated variables were then analysed with a statistical tool known as multichannel singular spectrum analysis (MSSA). We found that the subtropical gyre is not the largest contributor to the overall, basin-wide variability, in contrast to previous suggestions. The subpolar gyre and the inter-gyre region (the transition area between subpolar and subtropical gyres) also contribute with multipolar anomalies at multiple frequencies: these tend to cancel one another in terms of the basin-wide air-sea CO2 flux. We found a strong correlation between the air-sea CO2 fluxes and the North Atlantic Oscillation (NAO), but only if one takes into account time lags as does MSSA (maximum r=0.64 for lags between 1 and 3 years). The effect of increasing atmospheric CO2 (the anthropogenic perturbation) on total variability was negligible at interannual time scales, whereas at the decadal (13-year) time scale, it increased variability by 30%.

Statistical evaluation of data from tractor guidance systems - Peter K. Dunn; Andrew P. Powierski; Rodger Hill (Precision Agriculture, 2006)

A model for wave control on coral breakage and species distribution in the Hawaiian Islands - C. D. Storlazzi; E. K. Brown; M. E. Field; K. Rodgers; P. L. Jokiel (Coral Reefs, 2005)

Understanding the trophic role of the Antarctic ctenophore, Callianira antarctica, using lipid biomarkers - Se-Jong Ju; K. Scolardi; K. L. Daly; H. Rodger Harvey (Polar Biology, 2004)

Effects of habitat, wave exposure, and marine protected area status on coral reef fish assemblages in the Hawaiian archipelago - A. M. Friedlander; E. K. Brown; P. L. Jokiel; W. R. Smith; K. S. Rodgers (Coral Reefs, 2003)

Generation and sequence characterization of a normalized cDNA library from swine ovarian follicles - Alexandre R. Caetano; Rodger K. Johnson; Daniel Pomp (Mammalian Genome, 2003)

A maize bacterial artificial chromosome (BAC) library from the European flint inbred line F2 - D. M. O’Sullivan; P. J. Ripoll; M. Rodgers; K. J. Edwards (Theoretical and Applied Genetics, 2001)

Mineralogical and textural changes accompanying ageing of silica sinter - N. R. Herdianita; P. R. L. Browne; K. A. Rodgers; K. A. Campbell (Mineralium Deposita, 2000)

Characterization of magnetite particles in shocked quartz by means of electron- and magnetic force microscopy: Vredefort, South Africa - Marthinus Cloete; Rodger J. Hart; Herbert K. Schmid; Martyn Drury; Chris M. Demanet; K. Vijaya Sankar (Contributions to Mineralogy and Petrology, 1999)

Spin-state equilibria and axial ligand bonding in FixL hydroxide: a resonance raman study - Gudrun S. Lukat-Rodgers; K. R. Rodgers (JBIC Journal of Biological Inorganic Chemistry, 1998)

Fate of endothall during the Pat Mayse Lake (Texas) aquatic plant management program - K. H. Reinert; M. L. Hinman; H. Rodgers (Archives of Environmental Contamination and Toxicology, 1988)